Bradyrhizobium zhengyangense sp. nov., isype strains of the most closely related species ofolated from effective nodules of Arachis hypogaea L. in central China. Issue 3 (23rd March 2023) - Zhang, Junjie; Wang, Nan; Li, Shuo; Peng, Shanshan; Andrews, Mitchell; Zhang, Xiaoxia; Zhang, Yanming; Yu, Hui; Song, Jiangchun; Chen, Wenfeng; Wang, Entao; Li, Youguo
Abstract : Three slow-growing rhizobial strains (WYCCWR 12678, WYCCWR 12774 and WYCCWR 13023 T ) isolated from effective nodules of Arachis hypogaea L. (cultivated peanut) sampled in Zhengyang County, Henan Province, central China were characterized using a polyphasic approach. The three strains were assigned to the genus Bradyrhizobium based on phylogenetic analysis of their 16S rRNA sequences. Phylogenetic analysis based on their concatenated recA-glnII-gyrB-dnaK-rpoB gene sequences placed the strains into a distinct lineage. Whole-genome average nucleotide identity (ANI) values between WYCCWR 13023 T and WYCCWR 12774 and WYCCWR 12678 were 99.43 and 99.31% respectively. ANI values between WYCCWR 13023 T and the most closely related strains were all below 93 %. The digital DNA–DNA hybridization (dDDH) values between WYCCWR 13023 T and ' B. guangzhouense ' CCBAU 51670 T, B. manausense BR 3351 T and B. guangdongense CCBAU 51649 T, the three most closely related type strains, were 50.40, 43.50 and 39.20% respectively. Phenotypic characterization also allowed the differentiation of the novel strains from their most closely related type strains. Based on the genotypic and phenotypic features, we conclude that the three strains represent a novel species for which the name Bradyrhizobium zhengyangense sp. nov. is proposed, with WYCCWR 13023 T (=GDMCC 1.3180 T =HAMBI 3760 T ) as the type strain.